Characterization of mRNAs that map in the BglII N fragment of the herpes simplex virus type 2 genome. - Jenkins, F J (1984)
The BglII N DNA fragment (0.580 to 0.620 map units) of herpes simplex virus type 2 strain (333) is of interest because of its transforming potential. This fragment contains either partial or the complete coding sequences for nine mRNA transcripts that can be detected during a lytic infection. Subclones of the BglII N DNA fragment were generated in plasmid vectors, and the approximate locations of the mRNA transcripts were mapped by RNA blot hybridization technology. Precise 5' or 3' ends (or both) of these mRNA species were determined by S1 nuclease mapping, using the BglII N subclones as DNA probes. At least four mRNA transcripts are fully encoded in the BglII N fragment. The coding regions for all of the mRNA transcripts are densely packaged along the BglII N fragment with less than 150 base pairs between neighboring mRNA ends. Analysis of both neutral and alkaline gels failed to reveal the presence of any detectable introns. This manuscript reports a detailed transcription map for this region.